Physical Properties of Some Urban Trees for Carbon Dioxide Sequestration: a Case Study of a Residential Complex - Mohsen, Al-Zahraa A.; Abdulkareema, Asraa Khtan (Iraqi Journal of Science, 2026)
In recent years, there has been a significant urbanization of the world, including in Iraq, particularly in Baghdad. This has led to an increase in pollutants and greenhouse gas (GHG) emissions, particularly carbon dioxide (CO2). Therefore, it was necessary to find sustainable environmental solutions to reduce these gases, one of which is the biological sequestration of CO2 using trees. Therefore, this study aimed to calculate CO2 sequestration from trees using field data and biological methods for the Yamama City residential complex in Baghdad. The results showed that the complex's trees, numbering 3788, contributed to sequestering 197039.2 kg/year. This amount varies between four types (Conocarpus, Acacia, Albizia, and Palm), the largest contribution being Conocarpus trees, amounting to 18662.7 kg/year, which represents 95% of the total number of trees, and the least contribution being Acacia trees, amounting to 135.6 kg/year, which represents 2%. Since the sequestration quantities were calculated by field data for all trees and due to the difficulty of this method in measurement, the sequestration quantity was calculated using a modified method, and its accuracy was proven by calculating the correlation coefficient between the modified method values ​​and the actual values, which recorded r = 0.98. To know the effect of the physical properties of trees on the amounts of carbon dioxide sequestration, the effect of tree height and diameter was compared with the sequestration quantities, where it was found that the diameter has a greater effect, in addition to the fact that age has a direct relationship with the sequestration quantities. Finally, this study confirms the role of urban trees in reducing CO2 emissions and provides practical methods for sustainable urban planning in fast-growing cities such as Baghdad.